Biochemical, Histopathological, and Ophthalmologic Associations with Antibiotic Resistance in Helicobacter pylori Related Gastritis in Pediatric Surgical Patients - Mutee Ullah Majid, Anwar ul Haq, Afshan Zia, Hamid Nawaz Khokhar, M. Shakil Zari Khawri Siddiqui, Asma Arshad Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Helicobacter pylori infection is a major cause of chronic gastritis in children, and increasing antibiotic resistance poses a significant challenge to successful eradication. Persistent infection may lead not only to severe gastric mucosal inflammation but also to systemic biochemical disturbances and extra-gastric manifestations, including ocular surface involvement. Data integrating histopathological severity, biochemical alterations, ophthalmologic findings, and antibiotic resistance in pediatric surgical patients are limited. Objective: To evaluate the association of biochemical parameters, histopathological severity, and ophthalmologic findings with antibiotic resistance in H. pylori–related gastritis among pediatric surgical patients. Methods: This cross-sectional study was conducted at Nishtar Medical University, Multan, and Sahara Medical College, Narowal, from June 2022 to March 2023. A total of 100 pediatric patients (5–16 years) with histologically confirmed H. pylori gastritis were included. Gastric biopsies were assessed using the Updated Sydney System. Antibiotic resistance to clarithromycin and metronidazole was determined using biopsy-based methods. Biochemical markers including hemoglobin, serum ferritin, C-reactive protein, and albumin were measured. All patients underwent ophthalmologic evaluation focusing on ocular surface parameters. Results: Antibiotic resistance was observed in 72% of patients, with metronidazole resistance being most common. Resistant infections were significantly associated with higher histopathological severity scores, increased neutrophilic activity, and greater H. pylori density (p<0.001). Biochemically, resistant cases showed lower hemoglobin and ferritin levels and higher CRP concentrations (p<0.05). Ophthalmologic abnormalities, including reduced tear break-up time and increased meibomian gland dysfunction, were significantly more frequent in resistant infections. Conclusion: Antibiotic-resistant H. pylori gastritis in pediatric surgical patients is linked to more severe gastric inflammation, systemic inflammatory and iron-deficiency changes, and increased ocular surface dysfunction. These findings emphasize the need for susceptibility-guided therapy and a multidisciplinary approach to improve clinical outcomes in affected children. Keywords: Helicobacter pylori, pediatric gastritis, antibiotic resistance, histopathology, biochemical markers, ophthalmologic findings.